Fundraising : principles and practice - Worth, Michael J. (SAGE, 2016)
Fundraising: Principles and Practice provides readers with a comprehensive introduction to fundraising. Taking a balanced perspective, bestselling author Michael J. Worth offers insights on the practical application of relevant theory. The text is designed to engage readers in thinking critically about issues in fundraising and philanthropy to prepare them for careers in the nonprofit sector. Worth explores donor motivations and fundraising techniques for annual giving programs, major gift programs, planned giving, and corporate and foundation giving and campaigns. Traditional methods, including direct mail and personal solicitations, are discussed as well as new tools and practices, including online fundraising, crowd-funding and social networks, analytics, and predictive modeling. Written specifically for nonprofit career-oriented individuals, this book helps readers become successful fundraisers.- Resumé vydavatel
Keywords: fundraising; neziskové organizace; charitativní činnost; fund raising; nonprofit organizations; charities; elektronické knihy; monografie; electronic books; monographs